TREN DAN POLA PENELITIAN DALAM FINANCIAL TECHNOLOGY UNTUK MENINGKATKAN PENJUALAN UMKM : PERSPEKTIF BIBLIOMETRIK - Salsabila, Fira Fatma; Yuhertiana, Indrawati (STKIP Persada Khatulistiwa Sintang, 2025)
The internet has changed how people interact and get information. MSMEs have a hard time adopting fintech, which can cause problems like limited access to financial services, low levels of transaction efficiency, and difficulties in managing finances. This study looks at how publications on financial technology have developed.We used the Publish or Perish application with sources from Google Scholar to do a bibliometric analysis. We found 76 articles that we then analyzed using VOSviewer version 1.6.20 to create a visual map of the research. Research on financial technology in MSMEs is still important, especially because of technological developments that encourage MSMEs to continue adapting to the digital era.The relationship between financial technology and increased sales of MSMEs is a possible topic for future research. The study's limitation is that it only used the Publish or Perish application with the Google Scholar database. To improve the results, more keywords should be added in future studies.